Pycnodysostosis: Novel Variants in CTSK and Occurrence of Giant Cell Tumor - Shambhavi, Arya; Salian, Smrithi; Shah, Hitesh; Nair, Mohandas; Sharan, Krishna; Jin, Dong-Kyu; Cho, Sung Yoon; Mathew, Mary; Shukla, Anju; Girisha, Katta M. (Journal of Pediatric Genetics, 2018)
Pycnodysostosis is an autosomal recessive skeletal dysplasia caused by pathogenic variants in the cathepsin K (CTSK) gene. We report seven patients from four unrelated families with this condition in whom we have identified three novel pathogenic variants, c.120 + 1G > T in intron 2, c.399 + 1G > A in intron 4, and c.148T > G (p.W50G) in exon 2, and a known variant, c.568C > T (p.Q190*) in exon 5 of CTSK. We present the clinical, radiographic, and molecular findings of all individuals with molecularly proven pycnodysostosis from the present cohort. We also report the occurrence of giant cell tumor in the skull of a patient with this condition.
Keywords: pycnodysostosis; cathepsin K; giant cell tumor